DISCOVERY LEARNING IN CHRISTIAN RELIGIOUS EDUCATION TO INCREASE LEARNING ACHIEVEMENT - Fony Ticany Karina Sinta; Johni Hardori (Bethel Press, 2022)
The COVID-19 pandemic has changed the methods and accommodation of education. New and relevant methods should follow the transition from offline to online. However, this is not the case in all Christian Religious Education at Pusaka Abadi Elementary School class V. Many teachers still cannot implement appropriate online learning methods. This study aimed to implement the Discovery learning method during a pandemic. The research method used is classroom action research. The results showed that in the initial conditions, only 30% of students understood the material during the teaching and learning process at school. Then the researchers applied two methods, namely, cycle one and cycle two. Based on the research, the results of the first cycle increased by 60% after the discovery learning model was applied. In addition, the implementation of cycle II increased the results rapidly by 100%.